Social Transformation in the Platform Economy: A Critical Analysis of Legal Protection for Gig Economy Workers in the City of Pontianak - Rochman, Auliya; Mandala, Yoga; Zulkarnain, Zulkarnain; Miftah, Dani; Putra, Rafi Dwi Cahya (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to critically analyze the contribution of platform economy jobs to the income and economic stability of gig workers, examine the influence of legal status on access to social security, and assess the implications of work flexibility on the welfare of gig workers in Pontianak City. The growing phenomenon of the gig economy through platforms such as Gojek, Grab, Maxim, and ShopeeFood has opened up job opportunities for the community, but on the other hand, it has created unstable forms of employment with minimal legal protection. This study uses a qualitative approach by combining legal and sociological analysis. Primary data was obtained through in-depth interviews with drivers, couriers, labor unions, and officials from the Pontianak City Manpower Office. Secondary data was collected from labor regulations, official reports, and academic literature related to the platform economy. The results show that gig work contributes significantly to income, but is unstable due to long working hours, account performance, customer ratings, and non-transparent application algorithms. The status of workers as “partners” means that they have no social security, such as BPJS Ketenagakerjaan (Employment Social Security) and BPJS Kesehatan (Health Social Security), which must be borne entirely by the workers themselves. Furthermore, claims of work flexibility are proven to be illusory because workers are required to remain active to avoid a decline in orders ("anyep"). Job risks, including operational costs, accidents, and application penalties, are entirely borne by the workers. These findings emphasize the need for new, more inclusive policies to ensure legal and social protection for gig workers in Pontianak City.